Graphene Oxide Membranes with Heterogeneous Nanodomains for Efficient CO2 Separations. (4th October 2017) - Wang, Shaofei; Xie, Yu; He, Guangwei; Xin, Qingping; Zhang, Jinhui; Yang, Leixin; Li, Yifan; Wu, Hong; Zhang, Yuzhong; Guiver, Michael D.; Jiang, Zhongyi
Abstract: Achieving high membrane performance in terms of gas permeance and carbon dioxide selectivity is an important target in carbon capture. Aiming to manipulate the channel affinity towards CO2 to implement efficient separations, gas separation membranes containing CO2 ‐philic and non‐CO2 ‐philic nanodomains in the interlayer channels of graphene oxide (GO) were formed by intercalating poly(ethylene glycol) diamines (PEGDA). PEGDA reacts with epoxy groups on the GO surface, constructing CO2 ‐philic nanodomains and rendering a high sorption capacity, whereas unreacted GO surfaces give non‐CO2 ‐philic nanodomains, rendering low‐friction diffusion. Owing to the orderly stacking of nanochannels through cross‐linking and the heterogeneous nanodomains with moderate CO2 affinity, a GO‐PEGDA500 membrane exhibits a high CO2 permeance of 175.5 GPU and a CO2 /CH4 selectivity of 69.5, which is the highest performance reported for dry‐state GO‐stacking membranes.